Applying the Dual Filial Piety Model in the United States: A Comparison of Filial Piety Between Asian Americans and Caucasian Americans - Lim, Amy J.; Lau, Clement Yong Hao; Cheng, Chi-Ying (Frontiers in Psychology, 2022)
The definition and measurement of filial piety in existing research primarily focuses on the narrow conceptualizations of Asian filial piety, which would inflate cultural differences and undermine cultural universals in how people approach caring for their elderly parents. Employing the Dual Filial Piety Model (DFPM), this study aimed to examine the relationship between filial piety and attitude towards caring for elderly parents beyond the Asian context. In our study (N = 276), we found that reciprocal filial piety (RFP) does not differ across cultures while authoritarian filial piety (AFP) does. We also found that collectivism, rather than ethnicity, predicted RFP and AFP, which in turn predicted positive attitude towards caring for elderly parents. Our work demonstrates the cross-cultural applicability of the DFPM and highlights the universal and culture-specific aspects of filial piety.